2018
DOI: 10.1177/0031512518803203
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Flow, Mental Toughness, and Subjective Performance Perception in Various Triathletes

Abstract: This study examined the relationship between mental toughness (MT), subjectively perceived performance, and dispositional flow in a sample of 114 high-performing ironmen and standard distance triathletes ( Mage = 28.81 years, SD = 3.45) recruited from triathlon clubs. Participants completed the Mental Toughness Questionnaire, Dispositional Flow Scale, and self-rated subjectively perceived performance. Pearson’s correlations between these measures revealed a significant, positive relationship between global MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…These data concur with a recent review which indicated that MT represents one of the most important psychological attributes influencing athletic success (Cowden, ). This relationship between MT and success in sport is not only found when performance is assessed objectively, but also when the athlete assesses their own performance subjectively (Meggs, Chen & Koehn, ). It should be noted, however, that MT may be influenced by other psychological attributes such as task and ego orientation (Álvarez, Walker & Castillo, ).…”
Section: Discussionmentioning
confidence: 99%
“…These data concur with a recent review which indicated that MT represents one of the most important psychological attributes influencing athletic success (Cowden, ). This relationship between MT and success in sport is not only found when performance is assessed objectively, but also when the athlete assesses their own performance subjectively (Meggs, Chen & Koehn, ). It should be noted, however, that MT may be influenced by other psychological attributes such as task and ego orientation (Álvarez, Walker & Castillo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mental toughness in kickboxers correlated with the result obtained during competition [32]. Mental toughness indices were related to the subjectively assessed level of performance of triathletes and Ironman athletes [38] and the best time in triathlon competitions [22]. There was also a positive relationship between performance and mental toughness in adolescent women volleyball players [35].…”
Section: Effect Of Mental Toughness On Sporting Performancementioning
confidence: 99%
“…Gucciardi’s (2017) characterization recognizes both the traditional roots of MT and its contemporary application to a range of settings. These include sport (Meggs et al, 2018), education (Gerber et al, 2013a; St Clair-Thompson et al, 2015; Haghighi and Gerber, 2018), occupational (Marchant et al, 2009), and health (Coulter et al, 2010; Clough and Strycharczyk, 2012; Brand et al, 2014; Sadeghi Bahmani et al, 2016a; Kruger, 2018).…”
Section: Introductionmentioning
confidence: 99%